Nanoparticles targeting monocytes and macrophages as diagnostic and therapeutic tools for autoimmune diseases (2023)
ABSTRACT: Autoimmune diseases are chronic conditions that result from an inadequate immune response to self-antigens and affect many people worldwide. Their signs, symptoms, and clinical severity change throughout the course of the disease, therefore the diagnosis and treatment of autoimmune diseases are major challenges. Current diagnostic tools are often invasive and tend to identify the issue at advanced stages. Moreover, the available treatments for autoimmune diseases do not typically lead to complete remission and are associated with numerous side effects upon long-term usage. A promising strategy is the use of nanoparticles that can be used as contrast agents in diagnostic imaging techniques to detect specific cells present at the inflammatory infiltrates in tissues that are not easily accessible by biopsy. In addition, NPs can be designed to deliver drugs to a cell population or tissue. Considering the significant role played by monocytes in the development of chronic inflammatory conditions and their emergence as a target for extracorporeal monitoring and precise interventions, this review focuses on recent advancements in nanoparticle-based strategies for diagnosing and treating autoimmune diseases, with a particular emphasis on targeting monocyte populations.